Laser annealing of oxide capped Si/Ni nanowire - Lin, Juncheng. (2009)
Laser annealing of semiconductor nanowires has opened new possibilities for crystal growth, alloying and novel structure in the rapid miniaturization of microelectronics. The use of laser processing techniques offers a unique control of the heat flow into the material. Different beam delivery systems can be used to achieve a desired beam shape and laser fluence profile, which significantly influence the resulting microstructure of the material. In this thesis, excimer laser annealing (ELA) process is performed to achieve nickel silicide formation on silicon nanowire (SiNW). ELA is used for the activation of silicide formation as it can provide ultrafast annealing with a very limited thermal energy that is just enough to form silicide. However, in Ni-Si phase system, the phase formation is rather complex as it is depended on process parameters and substrate variations. It is observed that the phase NiSi has relatively low melting point (990°C) and low-resistivity (14µΩ-cm) which is desired to achieve in this experiment. The experiment is carried out on several samples with two different amount of Ni coated on them. All the samples are capped with a layer of oxide which may act as an addition heat entrapment centre for the NWs. Following on, they are annealed at different laser fluence level and number of pulses to find out the best condition to achieve Ni/Si nanowires with better electrical properties. The surface structures of annealed samples are analyzed using Scanning Electron Microscope (SEM) and Field Emission Scanning Electron Microscope (FESEM). Finally, the I-V characteristic for the annealed NWs is measured using four-pin probe station, and the resistance of the NWs will be determined.